2020
DOI: 10.1055/s-0040-1716781
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Mechanism of Action of Fluoridated Toothpaste Containing Proprietary REFIX Technology on the Remineralization and Repair of Demineralized Dental Tissues: An In Vitro Study

Abstract: Objectives This in vitro study aimed to characterize the mineral content and surface and cross-sectional morphology of enamel and dentin tissues treated with a 1450 ppm fluoride-containing toothpaste with REFIX technology. Materials and Methods Bovine enamel blocks (n = 5) were obtained (4 × 4 × 6 mm), demineralized (artificial caries lesion), and treated (pH cycling and brushing with the toothpaste). During the pH cycling, which lasted for 7 days (demineralization and remineralization took 6 and 18 hours, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 34 publications
3
11
0
Order By: Relevance
“…Furthermore, other products, including a gold standard one, would allow other comparisons. In spite of these limitations, with this in vitro study, the results of previous studies [16,27] corroborate with our results. Complementary studies are still necessary to evaluate, especially in in situ and in vivo studies, the effectiveness of REFIX-containing technology toothpaste to remineralize the enamel and dentin tissues.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, other products, including a gold standard one, would allow other comparisons. In spite of these limitations, with this in vitro study, the results of previous studies [16,27] corroborate with our results. Complementary studies are still necessary to evaluate, especially in in situ and in vivo studies, the effectiveness of REFIX-containing technology toothpaste to remineralize the enamel and dentin tissues.…”
Section: Discussionsupporting
confidence: 92%
“…The authors believe that the decrease in the sensitivity expressed by the participants could be due to deposition of crystals, which seems to progressively occlude the dentin tubules, reducing the dentinal fluid flow, and subsequently reducing the dentin hypersensitivity [12]. In another in vitro study [27], the mineral content and surface and cross-sectional morphology of enamel and dentin tissues treated with the same toothpaste were evaluated. The toothpaste with REFIX technology not only remineralized, but also effectively repaired the surface enamel.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated the formation of a silicon-enriched mineral layer on the enamel surface induced by the REFIX-based toothpaste was favored by the formation of complexes of the bioactive particles of calcium, phosphorus, and sodium. 14 Substituting PO 4 with SiO 4 is believed to affect the mechanical properties of the silicon-enriched hydroxyapatite in a dose-dependent manner, decreasing hardness and the elastic modulus. 29 Conversely, the silicon content in the toothpaste formulation in association with fluorine and phosphate groups induces increased bioactivity and apatite-forming ability of hydroxyapatite, which is enhanced by the substitution of silicon, or silicate, into the remineralizing hydroxyapatite.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, SDG contains the proprietary REFIX technology with experimental blue silica. REFIX technology-containing toothpaste was regarded to allow the formation of a silicon-enriched hydroxyapatite layer on the enamel surface [ 35 , 36 ]. Silica is a component of bioactive glass and acts as a nucleation site for calcium and phosphate ion precipitation in the formation of hydroxyapatite [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The differences in the outcomes observed in the present study support the speculation that chromatic changes of the enamel may occur due to the modification of the hydroxyapatite structure induced by the treatment with whitening toothpastes. As previously demonstrated [ 35 ], depending on the substitution at the sites of the hydroxyapatite structure, changes in calcium phosphate nucleation, hydroxyapatite growth and crystallization, and its stability may occur in an oral environment rich in ions released by the toothpaste [ 43 ]. In this manner, changes in the mineral phase of teeth may occur in terms of stoichiometric hydroxyapatite.…”
Section: Discussionmentioning
confidence: 99%